TECHNIQUE FOR EXPERIMENTAL STUDIES OF THE EFFECT OF SHOT IMPACT ACTION ON THE STATE OF METAL SURFACES - Brykun, O. N.; Chernyak, R. E.; Goryk, О. V. (Scientific Progress & Innovations, 2020)
One of the technological problems is poorly studied shot blasting, which is widely used in various branches of mechanical engineering, including agricultural, for surface preparation of machine metal parts and products for protective non-metallic coatings. The reliability and durability of such products by 80% depends on the quality of surface preparation by shot blasting. That is why the study of surfaces condition after theirs cleaning has the priority importance in the industrial production of metal products, especially those that are operated in aggressive environments. Analytical prediction of the quality of machine processed surfaces does not always give a reliable result due to the complexity of modeling mass impulse effect of attacking particles’ stream on an attacked metal obstacle, and in the majority of cases, is limited to the interaction of a separate spherical shot with it. Therefore the experimental determining of individual characteristics of short blasting process has practical importance, it is often decisive. The purpose of this article is to develop a methodology for conducting and obtaining individual results of experimental studies of shot blasting process of metal surfaces. To determine the influence of the initial parameters of the process (the angle and speed of attack, the diameter of the shot) on the geometry of the track left by the shot on the attacked surface the technique for studying the impact interaction of an individual shot with a flat plate steel sample is presented. The study was conducted in the laboratory of Poltava State Agrarian Academy on the developed installation (stand) using a single-shot pneumatic gun of the “ИЖ -53M” brand which was tested by the speed of the shot out from the muzzle using certified IБX-731 optoelectronic measuring complex. To determine the roughness of the treated surface, the degree of charging and the intensity of surface layer destruction, studies of the interaction with the surface of steel disc samples of shot-blasting torch were carried out on a modernized industrial installation at JSC “Poltava Automobile Aggregate Plant”. The samples were subjected to heat treatment in the normalization blasting mode in СНЗ-6.3 x 13 electric furnace.